Application of Bioinformatics in molecular data analysis for Leishmania major vector Phlebotomus papatasi sand fly - Omar Hamarsheh (My University, 2010)
Three molecular typing tools: multi-locus microsatellite typing, cytochrome b and internal
transcribed spacer II sequence analysis, have been evaluated using bioinformatics application
for their usefulness to infer population structure of P. papatasi sand flies. Microsatellite
markers showed high resolution power for differentiating globally distributed P. papatasi
populations, whereas analysis of cytochrome. b sequences provided insight into relationships
of closely related populations from the Mediterranean. Population structure, differentiation,
and demographic history among P. papatasi populations are important to understand patterns
of dispersal in this species and for planning appropriate control measures.

Three molecular typing tools: multi-locus microsatellite typing, cytochrome b and internal
transcribed spacer II sequence analysis, have been evaluated using bioinformatics application
for their usefulness to infer population structure of P. papatasi sand flies. Microsatellite
markers showed high resolution power for differentiating globally distributed P. papatasi
populations, whereas analysis of cytochrome. b sequences provided insight into relationships
of closely related populations from the Mediterranean. Population structure, differentiation,
and demographic history among P. papatasi populations are important to understand patterns
of dispersal in this species and for planning appropriate control measures.
Application of Bioinformatics in molecular data analysis for Leishmania major vector Phlebotomus papatasi sand fly